ChemInform Abstract: Easily‐Controlled Chemoselective Hydrogenation by Using Palladium on Boron Nitride. Issue 51 (17th December 2013) - Yabe, Yuki; Sawama, Yoshinari; Yamada, Tsuyoshi; Nagata, Saori; Monguchi, Yasunari; Sajiki, Hiranao
Abstract The reaction conditions are developed to achieve the selective hydrogenation of azides and alkynes.